Discontinuous modulation techniques for cascaded H-bridge static compensators - Liu, Qingxiang (Nanyang Technological University, 2024)
Modern power systems face challenges due to the increasing use of renewable energy sources. To overcome these challenges, cascaded H-bridge (CHB) static synchronized compensators (StatComs) have emerged as promising solutions. CHB StatComs offer the advantage of directly regulating grid voltage and power factor at medium and high voltage levels without the need for additional low-frequency transformers. However, in order to attain the desired medium and high voltage levels, a large number of H-bridge submodules (SMs) are required. Despite each individual SM processing a relatively low voltage, it has to carry the entire leg current. This results in significant switching loss that needs to be carefully considered to ensure thermal reliability and optimal system efficiency in CHB StatComs. Discontinuous pulsewidth modulation (DPWM) is a technique that has gained research attention for its ability to reduce switching loss. In CHB StatComs with a star configuration, DPWM is achieved by injecting a zero-sequence voltage (ZSV) between the neutral of the converter and system ground, which clamps a converter leg ac-side voltage to a fraction of its corresponding cluster voltage (sum of dc-side capacitor voltages per converter leg). The clamped converter leg stops switching, resulting in reduced switching loss. However, unlike two-level converters where a common dc-link is shared by three phases, the single-phase configuration of CHB StatComs, along with the use of floating capacitors in the dc-side of each SM, complicates the use of conventional DPWM methods. This complication is further exacerbated during grid imbalances, as the interaction between grid currents and the ZSV for DPWM can result in nonzero active power transfer to each leg, leading to divergence in cluster voltages and causing performance degradation. To solve this problem, the thesis focuses on developing advanced DPWM techniques that ensure effective cluster voltage control, even under severe grid imbalances, while simultaneously optimizing other control objectives, such as minimizing switching loss. The thesis first identifies a suitable DPWM method for CHB StatComs and analyzes its advantages in terms of capacitance reduction, switching loss reduction, enlargement of the inductive operation range, and reduction of converter voltage total harmonic distortion. The DPWM is then enhanced by considering the possibility of clamping to the zero-voltage level, providing benefits such as lower ZSV magnitude requirements and further reduction in switching loss. Subsequently, the thesis formulates DPWM as a finite-set optimization problem, proposing different cost functions to optimize the control objectives. This finite-set optimization formulation enables the embedding of cluster voltage control into DPWM implementation using model predictive control approaches, significantly enhancing the dynamical performance of CHB StatCom. The thesis evaluates the impact of the proposed DPWM methods on capacitor lifetime, highlighting the tradeoff between switching loss minimization and capacitor lifetime maximization. Finally, the thesis suggests future research directions, such as exploring increased clamping possibilities by considering the option of clamping to intermediate voltage levels. This novel concept has the potential to optimally address the aforementioned tradeoff between capacitor lifetime and converter switching loss. The thesis offers significant contributions to the field by effectively decoupling DPWM implementation from CHB StatCom cluster voltage control, making DPWM a feasible and reliable solution for next-generation CHB StatCom applications. Additionally, it introduces advanced DPWM strategies that allows the optimization of dedicated control objectives. Case studies demonstrate significant improvements when different control objectives are prioritized, such as a reduction of more than 45% in switching loss, an increase of over 10% in capacitor lifetime, an expansion of more than 50% in the inductive operation range, and a decrease of over 20% in dc capacitor capacitance compared to conventional sinusoidal pulsewidth modulation. The study of the thesis represents a crucial step towards fully leveraging the potential benefits of intelligently utilizing ZSV in CHB StatComs, thereby advancing CHB StatComs with improved reliability and efficiency performance. The findings presented in this thesis can benefit the design and operation of CHB StatComs, as well as other power system applications.